P314 WHEN TAKO–TSUBO TRAPS… NOT ONLY OCTOPUSES. (18th May 2022) - Spissu, P; Contini, F; Licciardi, M; Leoni, L; Fazzini, L; Angius, S; Perra, F; Secchi, S; Marchetti, M; Montisci, R
Abstract: The case we present involves a 75 years–old woman with no cardiological past medical history, who presented to our attention complaining of sudden onset thoracic pain associated with dyspnea, dry cough, nausea and an episode of vomit. She called 911 rapidly coming to our Hospital. In the Emergency room an EKG showed ST segment depression in the inferior leads and in the blood test a remarkable increase in HS–Troponin level was evident. An echocardiogram showed mid and apical left ventricle segments hypokinesia with moderately reduced Ejection Fraction (45%); notably, right ventricle was increased in dimension with moderate tricuspid regurgitation and mild pulmonary hypertension. Because of this last find, D–dimer was checked and a pulmonary angio– CT was performed which excluded active pulmonary embolism. Next day she underwent coronary angiography which showed no coronary lesion able to explain the clinical and echocardiographic presentation; left ventriculography was also performed showing an increase in end–systolic volume with hypokinesia of the anterolateral, apical and diaphragmatic walls and an Ejection Fraction (EF) of 30%. These findings allowed us to make the diagnosis of Tako–Tsubo syndrome, also known as stress–induced cardiomyopathy. Few days later, a cardiac magnetic resonance (CMR) was performed showing whole apical and antero–lateral mid ventricular hypokinesia with compensatory hyperkinesia of basal segments; T2–weighted sequences were positive at the hypokinetic segments with no specific Late Gadolinium Enhanced (LGE) images. What's more, an atrial septal defect type "ostium secundum" was clearly evident, causing a left–to–right shunt hemodynamically significant (Qp/Qs of about 2, 8) with right atrial and right ventricle dilatation. Pulmonary artery and its main branches were dilated too. After these findings, lady underwent right heart cardiac catheterization that reported a Qp/Qs of 3, 24 and a shunt flow of 8, 78 L/min, with a cardiac index of 2, 5 L/min/m2 and normal pulmonary vascular resistance (0, 7 Wood Units). Because of these measures the patient was discharged from our Cardiology Unit and referred to the Interventional Cardiology centre of our city for the percutaneous closure of the hemodynamically significant atrial septal defect. This case is curious because it shows how things in Cardiology can be deeply and unpredictably connected.